An Impact of Employee Performance in Enterprise Turnover Using Grid Based Machine Learning Model - Krishna, I. M. V.; Kannan, G.; Madhavi, N. Bindu; S., Shanthana; Thiruvenkadam, T.; Govindarajan, A. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The most important assets of most companies are their workers. Only with them is the value and management performance of the company calculated. And production and turnover are calculated based on their output. Therefore the performance of its employees is an important factor in evaluating a company and analyzing its potential. A grid algorithm has been designed with this in mind. Based on this, the input time of the workers employed by a company, the type of work, the one day production and the income available to the company through him are calculated. The company will then accurately calculate the following situations through machine learning algorithms that compute these data. It will also immediately calculate the nuances of dealing with employee performance deficiencies and effectively manage its data.